2021
DOI: 10.1111/hex.13323
|View full text |Cite|
|
Sign up to set email alerts
|

Preference‐based patient participation for most, if not all: A cross‐sectional study of patient participation amongst persons with end‐stage kidney disease

Abstract: Background Patient participation is considered central for good healthcare. Yet, the concept is not fully understood when it comes to patients' experiences of participation in conjunction with their preferences, particularly in long‐term healthcare. The aim of this study was to investigate the extent and variation of preference‐based patient participation in patients with end‐stage kidney disease (ESKD). Methods A cross‐sectional study was conducted with 346 patients in renal care. The main variables were pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 49 publications
(120 reference statements)
2
17
0
Order By: Relevance
“…Given preferences for bedside handover do not vary much, we suggest they might not be theoretically or empirically useful to measure. Other researchers have demonstrated that patient preferences for and reported behaviours of patient participation are often in concordance, 44 , 45 further supporting our survey that only measures behaviours.…”
Section: Discussionsupporting
confidence: 87%
“…Given preferences for bedside handover do not vary much, we suggest they might not be theoretically or empirically useful to measure. Other researchers have demonstrated that patient preferences for and reported behaviours of patient participation are often in concordance, 44 , 45 further supporting our survey that only measures behaviours.…”
Section: Discussionsupporting
confidence: 87%
“…International guidelines recommend incorporating patients' goals and preferences regarding modality and access into the decision‐making process 8‐10 . However, evidence suggests that a large proportion of patients and their healthcare professionals do not work collaboratively to reach decisions regarding dialysis modality, and many patients feel unprepared to engage in the decision‐making process regarding dialysis 18,19 …”
Section: Introductionmentioning
confidence: 99%
“…It comprises engagement around the clock and not just during “one health‐care moment” 13 . Furthermore, patient participation is considered central to good healthcare and to have a positive health outcome for patients 14 . Patient's involvement in care decisions regarding pressure ulcers is important.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Furthermore, patient participation is considered central to good healthcare and to have a positive health outcome for patients. 14 Patient's involvement in care decisions regarding pressure ulcers is important. However, many patients report that health care staff fail to establish a connection with them and to inform them about pressure ulcers.…”
Section: Introductionmentioning
confidence: 99%